Influence of Audio-Visual Media on Elderly Knowledge About Hypertensive Crisis Prevention - Prastiwi, Firman; Budiman, Amin Aji; Fitriyani, Noor; Rahmad, Muhamad Nur (Viva Medika, 2023)
Many of the physical and psychological changes that occur with age can have an impact on the prevalence of hypertension. The more common causes of hypertensive crisis are related to the knowledge of the elderly themselves, such as non-adherence to medication, ignorance related to lifestyle, and ignorance related to the concept of disease. An effective and easy way to increase the knowledge of the elderly is to use audio-visuals. The purpose of this study was to determine the effect of audio-visual media on the knowledge of the elderly about hypertension crisis prevention at the Sabar Hati Banyuanyar Nursing Home. This research is a quasi-experimental approach with a total sample of 50 elderly people divided into two groups. The research tool utilizes audio-visual media, research characteristic instruments, and knowledge instruments. For analysis, the Wilcoxon and Mann-Whitney tests were chosen because the data distribution was not normal. The results showed the effect of audio-visual media on the knowledge of the elderly in the intervention group (p value 0.011), with a median pre-intervention value of 6 to 7. The results of the Man Whitney test showed that there was no difference between pre (intervention-control) and post (control), with p values of 0.342 and 0.181, respectively. The conclusion of the study was that audio-visual media could lead to an increase in the knowledge of the elderly regarding the prevention of hypertensive crisis